1999
DOI: 10.1046/j.1365-2168.1999.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gallbladder cancer by radical resection

Abstract: With careful patient selection, radical resection for gallbladder cancer improves the prognosis with acceptable operative mortality and morbidity rates, even for stage IV disease, provided that complete gross tumour resection is combined with radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 8 publications
5
109
1
6
Order By: Relevance
“…More and more people advocated extended radical cholecystectomy in patients of medium and advanced stage in order to improve the long-term survival. Todoroki et al (1999) reported that on the basis of simple cholecystectomy, complicated with surgical procedures including hepatic lobe resection, semi-hepatectomy, pancreaticoduodenectomies, partial gastrectomy or colectomy, the 5-year postoperative overall survival rate was around 25%-33% . Similarly, Sasaki et al (2006) reported that the 5-year overall survival rate of gallbladder cancer patients of Nvein IV stage who underwent expanded radical surgery was around 42.9% .…”
Section: Discussionmentioning
confidence: 99%
“…More and more people advocated extended radical cholecystectomy in patients of medium and advanced stage in order to improve the long-term survival. Todoroki et al (1999) reported that on the basis of simple cholecystectomy, complicated with surgical procedures including hepatic lobe resection, semi-hepatectomy, pancreaticoduodenectomies, partial gastrectomy or colectomy, the 5-year postoperative overall survival rate was around 25%-33% . Similarly, Sasaki et al (2006) reported that the 5-year overall survival rate of gallbladder cancer patients of Nvein IV stage who underwent expanded radical surgery was around 42.9% .…”
Section: Discussionmentioning
confidence: 99%
“…In fact 5-year survival rates of 15–63% and 7–25% have been reported for T3 and T4 tumours, respectively (table 8) [3,10,11,12,13,14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 3-year DFS and OS rates in the patients that had undergone surgery alone without adjuvant therapy were 33% and 25.3%, respectively. Todoroki et al defended the viewpoint that radical cholecystectomy can be performed even in stage-IV disease [28] . Poor prognosis after surgery alone has brought forward chemotherapy and/or radiotherapy as adjuvant settings.…”
Section: Resultsmentioning
confidence: 99%